Corundum mullite ceramic material, molybdenum metal heterogeneous component and brazing manufacturing method and application of corundum mullite ceramic material and molybdenum metal heterogeneous component
By using corundum mullite ceramic materials and brazing manufacturing methods, the problems of low connection strength, poor reliability and poor thermal shock resistance in the thermoelectric conversion device are solved, and heterogeneous components with high strength, reliability and thermal shock resistance are achieved, which are suitable for the thermoelectric conversion device of nuclear reactors.
Patent Information
- Application Number
- CN202411776843.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The existing heterogeneous molybdenum metal and alumina ceramic components have problems such as low connection strength, poor reliability, and poor thermal shock resistance in the thermoelectric conversion device. Especially during rapid heating and cooling, failures such as cracking, peeling or breaking are prone to occur, which affects the performance and safety of the device.
Corundum mullite ceramic material is used as the insulating material, and by adjusting the addition amount and sintering temperature of corundum fine powder, ceramic material with a bending strength of ≥500MPa and a thermal shock resistance of ≥80%, and connected to molybdenum metal through brazing manufacturing method to form heterogeneous components with high connection strength and stable and reliable connection strength.
It improves the connection strength and reliability of molybdenum metal and ceramic heterogeneous components, enhances thermal shock resistance, maintains stable electrical properties under high temperature environments, reduces thermal stress and strain, avoids brittle fracture and deformation, and extends service life.
Smart Images

Figure CN119569432A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to brazing technology, in particular to a corundum-mullite ceramic material, a molybdenum metal heterogeneous component and a brazing manufacturing method and application thereof. Background Art
[0002] In nuclear power, the heat generated by the nuclear reactor is transferred to the thermoelectric conversion device through a heat exchanger. Thermoelectric conversion devices use the temperature difference effect to convert thermal energy into electrical energy, thereby achieving effective energy utilization and conversion. The material composition of thermoelectric conversion devices mainly includes two parts: thermoelectric materials and auxiliary materials. In addition to thermoelectric materials, thermoelectric conversion devices also require some auxiliary materials to complete their overall structure and function. These auxiliary materials include thermal conductive materials, insulating materials, electrode materials, etc. Their role is to ensure that the thermoelectric conversion device can maintain stable performance and safety during operation.
[0003] In thermoelectric converters, molybdenum metal is mainly used as an electrode material. Electrodes are key components in thermoelectric converters, responsible for collecting and transmitting current generated by the thermoelectric effect. Molybdenum metal is an ideal material for electrodes in thermoelectric converters due to its high electrical conductivity, high thermal stability and good mechanical properties. The high electrical conductivity of molybdenum metal ensures that the electrode can effectively collect and transmit current, reducing energy loss. At the same time, its high thermal stability enables the electrode to operate stably for a long time in a high temperature environment without deformation or damage due to high temperature. In addition, the good mechanical properties of molybdenum metal also enhance the durability and reliability of the electrode.
[0004] Ceramics are mainly used as insulating materials in thermoelectric conversion devices. With its excellent insulating properties, ceramic materials play a key role in preventing current leakage and ensuring safe and stable operation of equipment in thermoelectric conversion devices. Its high resistivity characteristics enable ceramics to effectively prevent the passage of current, thereby avoiding leakage or short circuit. In addition, ceramics also have good thermal stability and chemical stability, and can maintain stable insulating properties under high temperature and harsh chemical environments. These characteristics make ceramics an ideal insulating material in thermoelectric conversion devices. At the same time, ceramic materials also have high mechanical strength, can resist external shock and vibration, and protect the structural integrity of thermoelectric conversion devices. Alumina ceramics have good insulating properties, which help to achieve safe transmission and distribution of electrical energy in thermoelectric conversion devices. At the same time, the high temperature resistance of alumina ceramics also enables it to maintain stable electrical properties in high temperature environments, ensuring the normal operation of thermoelectric conversion devices under high temperature conditions. Therefore, alumina ceramics are mostly used as insulating ceramic sheets in nuclear power thermoelectric conversion devices.
[0005] Existing molybdenum metal and alumina ceramic heterogeneous components are usually connected by brazing. However, due to the large difference in thermal expansion coefficient and elastic modulus between the two, thermal mismatch occurs, which will generate large residual stress at the joint. Moreover, after the brazing material melts into liquid metal, it is difficult to wet the ceramic surface, resulting in low connection strength and poor reliability of the molybdenum metal and ceramic heterogeneous components when used in thermoelectric conversion devices. In addition, when molybdenum metal and alumina ceramic heterogeneous components are used in thermoelectric conversion devices, they may undergo a process of rapid heating and cooling, which may cause thermal stress inside the alumina ceramic and even failure phenomena such as cracking, peeling and even fracture. This will not only affect the performance and efficiency of the thermoelectric conversion device, but may also cause safety hazards.
[0006] The existing common corundum mullite ceramic is a ceramic material with corundum and mullite as the main crystal phases. It has high mechanical strength, good insulation performance and stable dielectric properties. Its relative dielectric constant is usually between 6 and 7, the dielectric loss tangent value is low, and the volume resistivity is high. 2 O 3 and SiO 2 The components first react with the Ti element in the solder alloy to form a TiO phase, and then the Al element in the ceramic and the Cu element in the solder alloy combine with TiO to form a Ti 3 (Cu, Al) 3 O phase, realizes the metallurgical bonding of ceramics and brazing alloy, and has good wettability. In addition, the existing corundum mullite ceramic material has strong chemical erosion resistance, good thermal stability, and can withstand rapid cooling and heating without easy peeling. However, when the existing ordinary corundum mullite ceramic is used in thermoelectric conversion devices, especially in thermoelectric conversion devices for nuclear reactors, there are problems such as reduced strength of corundum mullite ceramics under rapid cooling and heating conditions, poor joint reliability, and short service life. Summary of the invention
[0007] Therefore, in order to solve the problems of low connection strength, poor reliability, poor thermal shock resistance, etc. between molybdenum metal and alumina ceramic heterogeneous components in existing thermoelectric conversion devices, the present invention provides a corundum mullite ceramic material that can be used as an insulating material for a nuclear reactor thermoelectric conversion device.
[0008] To this end, the present invention provides a corundum-mullite ceramic material, which is mainly composed of corundum and mullite crystal phases, and is made of corundum micropowder and mullite particles through high-temperature sintering. The corundum-mullite ceramic has a bending strength of ≥500MPa, and a thermal shock resistance of ≥80% after 100 times of extreme cooling in air at room temperature-1000℃. 2 O 3 , the chemical formula of mullite is 3Al 2 O3 ·2SiO 2 .
[0009] In the preparation process of corundum mullite ceramic material, the amount of raw materials used affects its thermal shock resistance, high temperature insulation, strength and other properties. Preferably, the mass proportion of the corundum micropowder used is 26%-32%, the thermal shock resistance is 81%-89%, and the bending strength is 530-600MPa. The particle size of the mullite particles is 180-200 mesh, and the particle size of the corundum micropowder is 200-240 mesh.
[0010] Among them, in the present invention, the mass ratio of the amount of corundum micropowder refers to the mass percentage of the amount of corundum micropowder used in the total amount of corundum micropowder and mullite particles used in the preparation process of the corundum-mullite ceramic material, hereinafter referred to as "the amount of corundum micropowder added". The performance tests of various materials in the present invention, unless otherwise specified, refer to the performance at room temperature. "Normal temperature" in the present invention refers to 20℃-30℃. The "room temperature-1000℃ air extreme cooling 100 times" used in the present invention refers to rapidly cooling the corundum-mullite ceramic material to room temperature 100 times at 1000℃.
[0011] The sintering temperature and sintering time mainly affect the bonding strength of the corundum powder and mullite particles in the corundum-mullite ceramic material, thereby affecting the thermal shock resistance of the corundum-mullite ceramic material. Therefore, preferably, the sintering temperature is 1500°C-1700°C and the sintering time is 2.5-3h.
[0012] The thermal shock resistance R of the corundum-mullite ceramic material is directly related to the amount of corundum powder added ω, the sintering temperature T of its formation process, etc. In order to further ensure that the corundum-mullite ceramic material has good mechanical properties such as strength, toughness and impact resistance, it also has good thermal shock resistance; the relationship between the thermal shock resistance R of the corundum-mullite ceramic material and the amount of corundum powder added ω and the sintering temperature T therein satisfies the following formula:
[0013] R=R 0 +1.34T+3.2ω-4.2×10 -4 T 2 -0.052ω 2
[0014] Among them, thermal shock resistance R, %; T is temperature, ℃; ω is the amount of corundum powder added, %; R 0 =-1030.
[0015] The second object of the present invention is to provide a method for manufacturing a corundum mullite ceramic-molybdenum metal heterogeneous component, which mainly uses a welding method to obtain a brazed joint (the area where the corundum mullite ceramic and the molybdenum metal are brazed together) with high connection strength and stable and reliable corundum mullite ceramic material and molybdenum metal. Specifically, the manufacturing method includes the steps of:
[0016] Roughening pretreatment: roughening the surface of the corundum-mullite ceramic material to obtain a roughened ceramic material;
[0017] Brazing: brazing the roughened ceramic material and molybdenum metal with a brazing material to obtain the corundum mullite ceramic-molybdenum metal heterogeneous component. The brazing treatment is a heating brazing heat treatment, the heating temperature is preferably 890-910°C, and the holding time is preferably 20-30 minutes.
[0018] The third object of the present invention is to provide a corundum mullite ceramic-molybdenum metal heterogeneous component obtained by the brazing manufacturing method, wherein the brazing joint strength at the welding interface of the corundum mullite ceramic material and the molybdenum metal is ≥350MPa. The heterogeneous component has good thermal shock resistance, excellent mechanical properties and high temperature performance, exhibits good electrical insulation stability at high temperatures, can withstand large thermal stress and strain, is not prone to brittle fracture and deformation, can be used in thermoelectric conversion devices, and can solve the problems of low strength and poor reliability of the connection between the corundum mullite ceramic material and the molybdenum metal in the thermoelectric conversion device of the nuclear reactor.
[0019] Specifically, the heterogeneous component includes the above-mentioned corundum mullite ceramic material and molybdenum metal welded to the corundum mullite ceramic material.
[0020] The fourth object of the present invention is to provide an application of the above-mentioned corundum mullite ceramic-molybdenum metal heterogeneous component in a thermoelectric conversion device, especially in the field of nuclear power.
[0021] A thermoelectric conversion device for nuclear power comprises the above-mentioned corundum mullite ceramic-molybdenum metal heterogeneous component, wherein the molybdenum metal in the heterogeneous component is an electrode and the corundum mullite ceramic material is an insulating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a relationship diagram between the thermal shock resistance of the corundum-mullite ceramic provided by the embodiment of the present invention and the amount of corundum micropowder added and the sintering temperature;
[0023] Figure 2 is a microscopic photograph of the corundum-mullite ceramic material M2 provided in an embodiment of the present invention;
[0024] Figure 3This is a microstructure diagram of a brazed joint of a corundum-mullite ceramic-molybdenum metal heterogeneous component S2 after rapid air cooling at room temperature-1000° C. for 100 times provided by an embodiment of the present invention;
[0025] Figure 4 It is a microstructure diagram of the brazed joint of the alumina ceramic-molybdenum metal component D8 after rapid air cooling provided as a comparative example. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0027] The terms used in the present invention are all commonly used in the relevant field, and the raw materials, equipment, preparation processes, testing methods, etc. used are all prior art in the relevant field unless otherwise specified. The materials used are also commercially available.
[0028] In order to solve the problems, the first purpose of the present invention is to provide a corundum mullite ceramic material with good thermal shock resistance, which can be used as an insulating material for a nuclear reactor thermoelectric conversion device to solve the problems of low connection strength, poor reliability, and poor thermal shock resistance of heterogeneous components of molybdenum metal and alumina ceramic in existing thermoelectric conversion devices.
[0029] Specifically, a corundum-mullite ceramic material is mainly composed of corundum and mullite crystal phases, and is made of corundum micropowder and mullite particles through high-temperature sintering. The flexural strength of the corundum-mullite ceramic is ≥500MPa, and the thermal shock resistance of the room temperature-1000℃ air extreme cold 100 times is ≥80%. Among them, the main component of corundum in this article is α-Al 2 O 3 , the chemical formula of mullite is 3Al 2 O 3 ·2SiO 2 The purity of the mullite and corundum is ≥99.5%. Preferably, the corundum powder is imported plate-shaped corundum or high-purity fused corundum.
[0030] The amount of corundum powder added and the sintering temperature have important effects on the thermal shock resistance, high temperature insulation, bending strength and other properties of corundum mullite ceramics. When the amount of corundum powder added is 26%-32%, the SiO 2 -Al 2 O 3 The low eutectic point of the phase, at this time, the thermal shock stability and high temperature insulation of the corundum mullite ceramic material are good. When the amount of corundum micropowder added is too large or too small, the internal thermal expansion mismatch of the corundum mullite ceramic material is low, and there are fewer microcracks. Since the microcracks can absorb the fracture energy of the ceramic, when the amount of corundum micropowder added is too large or too small, it is not conducive to improving the thermal shock resistance of the corundum mullite ceramic material while ensuring other properties.
[0031] As the sintering temperature increases, the thermal shock stability of corundum mullite ceramics usually shows a trend of first increasing and then decreasing. At an appropriate sintering temperature, the crystal structure inside the ceramic is optimized, and the grain boundary bonding force is enhanced, thereby improving its thermal shock resistance. However, when the sintering temperature is too high, the crystal structure inside the ceramic may be destroyed, resulting in a decrease in thermal shock stability. Prolonging the sintering time can make the crystal structure inside the ceramic more perfect and the grain boundary bonding force more firm, thereby improving its thermal shock resistance. However, too long a sintering time may also cause defects such as too many pores and cracks inside the ceramic, which in turn reduces its thermal shock resistance. Therefore, the sintering temperature is preferably 1500℃-1700℃, and the sintering time is 2.5-3h.
[0032] When the particle size of corundum micropowder and mullite particles is too small, a sufficient number of microcracks cannot be formed inside the corundum mullite ceramic. Since the microcracks can absorb the fracture energy of the ceramic, the particle size of corundum micropowder and mullite particles is too small to improve the thermal shock resistance of the corundum mullite ceramic. When the particle size of corundum micropowder and mullite particles is too large, it is not conducive to the formation of a good combination of corundum micropowder and mullite particles, the pores and defects of the ceramic increase, and the thermal shock resistance decreases. Therefore, the particle size of the corundum micropowder is preferably 180-200 mesh, and the particle size of the mullite is preferably 200-240 mesh.
[0033] Thermal shock resistance refers to the ability of a material to maintain a stable structure without damage or failure when subjected to rapid temperature changes. The air quenching method was used to test the thermal shock resistance of corundum mullite ceramic materials. The corundum mullite ceramic materials were quenched to room temperature 100 times at 1000°C, and the retention rate of the flexural strength of the corundum mullite ceramic materials compared to the flexural strength before quenching was used as the thermal shock resistance index. The study found that the thermal shock resistance R of the corundum mullite ceramic material is directly related to the amount of corundum micropowder added in its raw material ω, the sintering temperature T of its preparation process, etc., and satisfies the following formula:
[0034] R=R 0 +1.34T+3.2ω-4.2×10 -4 T 2 -0.052ω 2
[0035] Among them, thermal shock resistance R, %; T is temperature, ℃; ω is the amount of corundum powder added, %; R 0 =-1030.
[0036] To ensure that the corundum-mullite ceramic material has good thermal shock resistance, the amount of corundum powder added ω is preferably 26%-32%, the sintering temperature T is preferably 1500°C-1700°C, and the thermal shock resistance R is preferably 81%-89%.
[0037] The above-mentioned corundum mullite ceramics have excellent mechanical properties such as strength, toughness, impact resistance, etc., with a small thermal expansion coefficient and high thermal conductivity, so they have good thermal properties and are suitable for applications in high temperature environments. The flexural strength of corundum mullite ceramics can reach 570MPa at 1300°C, and the fracture toughness KIC can reach 5.7MPa, both of which are 1.6 times higher than at room temperature. In this way, the strength and toughness not only do not decay but increase significantly with increasing temperature, which is an excellent characteristic of corundum mullite ceramics as high-temperature materials. The thermal shock resistance of corundum mullite ceramics is one of its important physical properties. Corundum and mullite as the main crystal phases make the above-mentioned corundum mullite ceramics have excellent thermal shock resistance. Specifically, the above-mentioned corundum mullite material can be repeatedly used 100 to 200 times at a higher temperature, such as 1000°C, without being easily peeled off or damaged.
[0038] The second main purpose of the present invention is to provide a brazing manufacturing method for a corundum mullite ceramic-molybdenum metal heterogeneous component. The brazing manufacturing method mainly comprises pre-treating the above-mentioned corundum mullite ceramic material by roughening, and then brazing it with molybdenum metal to obtain a corundum mullite ceramic and molybdenum metal brazing joint with high connection strength, stability and reliability.
[0039] Specifically, a brazing manufacturing method of a corundum-mullite ceramic-molybdenum metal heterogeneous component comprises the steps of:
[0040] Roughening pretreatment: roughening the surface of the corundum-mullite ceramic material to obtain a roughened ceramic material;
[0041] Brazing: The roughened ceramic material and the molybdenum metal are brazed with a brazing material to obtain the corundum-mullite ceramic-molybdenum metal heterogeneous component.
[0042] After the brazing material is melted into liquid metal, it is difficult to wet the surface of the corundum mullite ceramic. In order to obtain a high-strength corundum mullite ceramic and molybdenum metal brazing joint, the main purpose of the roughening pretreatment is to increase the surface roughness of the corundum mullite ceramic, increase its subsequent contact area with the melted brazing material, and make part of the brazing material penetrate into the corundum mullite ceramic after the brazing alloy melts, and form a good metallurgical bond with the corundum mullite ceramic, thereby improving the connection strength and reliability of the brazing joint. Therefore, the surface roughness of the roughened ceramic material obtained after the roughening pretreatment is 0.5-1μm. Further, in the step of the roughening pretreatment, the surface roughness of the corundum mullite ceramic can be increased by sandpaper grinding the surface of the corundum mullite ceramic, such as grinding with 180 mesh sandpaper.
[0043] In the brazing treatment step, the brazing material includes Zr: 26-29%, Ni: 21-24%, Cu: 21-24%, and the balance is Ti, in terms of mass percentage; it can be represented by TiZrCuNi brazing filler metal. The brazing material can be a TiZrCuNi foil brazing filler metal. If the thickness of the TiZrCuNi foil is less than 0.09mm, it is easy to make the brazing seam thickness too thin, which is not conducive to the combination of corundum mullite ceramics and molybdenum metal; if the thickness of the TiZrCuNi foil exceeds 0.1mm, it is easy to make the brazing seam thickness too thick, wasting brazing filler metal. Therefore, the thickness of the TiZrCuNi foil is preferably 0.09-0.1mm.
[0044] The brazing process comprises the following steps:
[0045] Component assembly and fixing: assembling and fixing the roughened ceramic material and the molybdenum metal together to form an assembly component;
[0046] Brazing heating: using a vacuum brazing furnace to heat and weld the assembly components to form a welding joint and obtain a semi-finished heterogeneous welded component;
[0047] Cooling and post-processing: The heterogeneous welded component semi-finished product is cooled to room temperature and post-processed to obtain the corundum mullite ceramic-molybdenum metal heterogeneous component.
[0048] The steps of assembling and fixing the components are prior art and may include: first assembling the roughened ceramic material and the molybdenum metal together, placing the brazing material between the roughened ceramic material and the molybdenum metal, maintaining a certain position and spacing; then fixing them with tools such as clamps or brackets to ensure that no movement or deformation occurs during the brazing process, thereby obtaining an assembled component.
[0049] The brazing heating step includes: placing the above-mentioned assembly into a vacuum brazing furnace, heating and welding, forming the welding joint at the connection between the roughened ceramic material and the molybdenum metal, and obtaining the heterogeneous welded component semi-finished product. Among them, the selection of the welding heating temperature is related to the liquidus temperature of the brazing material. According to the liquidus temperature of the brazing material TiZrCuNi, the heating temperature is preferably 890-910°C. If the heating temperature is lower than 890°C, the brazing material is not completely melted; if it is higher than 910°C, the heating temperature is too high, which affects the performance of the parent material, and the stress of the welding joint is large, thereby affecting the connection strength and reliability of the welding joint. The holding time is determined based on the TiZrCuNi brazing material and the parent material. If the holding time is too short, the brazing joint will have serious organizational segregation, uneven component distribution, and low joint strength; if the holding time is too long, it will cause excessive diffusion between the parent material and the brazing material, affecting the performance of the parent material; therefore, the holding time is preferably 20-30 minutes.
[0050] The cooling and post-processing steps include: first gradually cooling the heterogeneous welded component semi-finished product to room temperature; and then performing trimming, polishing, and other treatments on the brazing connection parts to obtain the molybdenum metal and ceramic heterogeneous components. During the cooling process, if the cooling rate is higher than 10°C / min, the residual stress of the weld joint is too large; if the cooling rate is lower than 5°C / min, the cooling time is too long and the preparation efficiency is too low; therefore, the cooling rate is preferably 5°C / min-10°C / min.
[0051] The manufacturing method provided by the present invention firstly roughens and grinds the surface of the corundum mullite ceramic to increase the surface roughness, so that during the brazing process, after the brazing material alloy melts, part of the brazing material penetrates into the interior of the corundum mullite ceramic material and forms a good metallurgical bond with the corundum mullite ceramic material; this is conducive to improving the mechanical strength of the welded joint of the corundum mullite ceramic-molybdenum metal heterogeneous component to reach 350-380MPa.
[0052] The third object of the present invention is to provide a corundum mullite ceramic-molybdenum metal heterogeneous component manufactured by the above brazing manufacturing method, wherein the brazing joint strength at the brazing interface of the corundum mullite ceramic material and the molybdenum metal is ≥350MPa. Wherein, the structural relationship between the corundum mullite ceramic material and the molybdenum metal needs to be determined according to the design structure of the heterogeneous component.
[0053] After testing, it was found that after 100 times of room temperature-1000℃ air quenching test, the brazing connection between the corundum mullite ceramic material and the molybdenum metal was well brazed without pores and cracks; the ceramic side had a dense structure, and there were no cracks between the brazed joint area and the corundum mullite ceramic side; the bending strength of the brazed joint at room temperature was 360-390MPa, and the fracture toughness KIC was 5.2-5.4MPa; after 100 times of quenching, the bending strength of the brazed joint was 290-340MPa, and the thermal shock resistance was 81-89%, etc., which met the requirements of the thermoelectric conversion device for the thermal shock resistance of materials.
[0054] A fourth object of the present invention is to provide an application of the above-mentioned heterogeneous component in a thermoelectric conversion device, especially in a thermoelectric conversion device for nuclear power.
[0055] A thermoelectric conversion device for nuclear power comprises the above-mentioned heterogeneous component, wherein the molybdenum metal in the heterogeneous component is an electrode and the corundum mullite ceramic material is an insulating layer.
[0056] Among them, the thermal shock resistance test method in the present invention is as follows:
[0057] First, the normal object to be tested is tested for bending strength to obtain the original bending strength; then the object to be tested is rapidly cooled from 1000°C to room temperature 100 times by air quenching method; then the bending strength of the object to be tested after air quenching is tested. The object to be tested can be a high-temperature insulating material such as corundum mullite ceramics, alumina ceramics, or a heterogeneous component of molybdenum metal and ceramics.
[0058] The flexural strength used in the present invention is tested according to GBT 11363-2008, the weld joint strength is tested according to GBT11363, the fracture toughness is tested according to "American Society for Testing and Materials Standard ASTM C1421-01a Standard for Determination of Fracture Toughness of Advanced Ceramics at Room Temperature"; and the thermal expansion coefficient is tested according to "GBT 16535 Test Method for Thermal Expansion Coefficient of Engineering Ceramics".
[0059] The present invention will be further explained with reference to specific embodiments below.
[0060] Example 1 Corundum Mullite Ceramic Material
[0061] This embodiment provides a corundum-mullite ceramic material M1-M5, which has corundum micropowder and mullite particles as the main crystal phase, and is made by mixing corundum micropowder and mullite particles as raw materials and sintering them in a high-temperature kiln at high temperature. Among them, the amount of corundum micropowder added and the sintering temperature have an important influence on the thermal shock resistance.
[0062] 1.1 Influence of process parameters on thermal shock resistance
[0063] The corundum-mullite ceramic materials with different total alumina contents and sintering temperatures in the raw materials were prepared by the controlled variable method and their thermal shock resistance was tested to screen and determine the appropriate amount of corundum powder added and sintering temperature. The specific experimental method includes: first, the corundum powder and mullite are evenly mixed in a high-temperature kiln according to a mass ratio of 26-32:68-74 and sintered at a high temperature of 1500℃-1700℃ to obtain the corundum-mullite ceramic material; then the thermal shock resistance of the corundum-mullite ceramic is tested, and the test results are fitted. Among them, some experimental data of the thermal shock resistance test are shown in Table 1, and the test data fitting results are shown in Table 1. Figure 1 shown.
[0064] Table 1 Preparation process parameters and thermal shock resistance results of corundum mullite ceramics
[0065]
[0066]
[0067] From Table 1 and Figure 1It can be seen that: under the same conditions, within 1500℃-1700℃, the thermal shock resistance of corundum mullite ceramic material basically increases with the increase of sintering temperature first, and then decreases with the increase of sintering temperature. Under the same conditions, when the amount of corundum micropowder added is controlled within 26%-32%, the thermal shock resistance of corundum mullite ceramic material basically increases with the increase of alumina content first, and then decreases with the increase of alumina content. Combining Table 1 and Figure 1 The change law of thermal shock resistance of corundum-mullite ceramic materials was analyzed. When the alumina content in the material is 30.8% and the calcination temperature is 1600℃, the thermal shock resistance of corundum-mullite ceramic materials is the best.
[0068] Combination Figure 1 The fitting empirical formula of the thermal shock resistance R of the above-mentioned corundum-mullite ceramics, the amount of corundum powder added ω, and the sintering temperature T is:
[0069] R=R 0 +1.34T+3.2ω-4.2×10 -4 T 2 -0.052ω 2
[0070] Among them, thermal shock resistance R, %; T is the sintering temperature, ℃; ω is the amount of corundum powder added, %; R 0 =-1030.
[0071] 1.2 Fitting formula verification
[0072] This experiment provides corundum mullite ceramic materials M1-M3 respectively. First, according to the process parameters shown in Table 2 and Table 3 and the above method provided in this experiment, the following corundum mullite ceramic materials M1-M5 are sintered at high temperature respectively. The seismic resistance, fracture toughness, thermal expansion coefficient, high-temperature insulation, etc. of the samples M1-M5 are tested respectively, and the test results are compared with the calculated results of the formula. The rationality is verified through the error.
[0073] In order to further verify the rationality of the above fitting formula, the following experimental scheme is designed:
[0074] Table 2 Fitting formula verification test results
[0075]
[0076] Table 2 shows that the error between the test value and the calculated value of the seismic resistance does not exceed ±0.20%, thus proving the scientificity and rationality of the above fitting formula.
[0077] 1.3 Ceramic material comparison
[0078] Ceramic material comparative examples 1-7 each provide a corundum mullite ceramic material DM1-DM7, which is substantially the same as the corundum mullite ceramic material M2 provided in Example 1, the main difference being that the raw materials and method parameters of each comparative example are different, as specifically shown below:
[0079] Comparative Example DM1: This comparative example uses natural corundum and natural kaolin as raw materials, and other methods and process parameters are the same as those of material M2;
[0080] Comparative Example DM2: The raw material corundum powder used in this comparative example is added in an amount of 15%, and other methods and parameters are the same as those of material M2;
[0081] Comparative Example DM3: The raw material corundum powder used in this comparative example is added in an amount of 45%, and other methods and parameters are the same as those of material M2;
[0082] Comparative Example DM4: In this comparative example, the sintering temperature of the mixture of mullite particles and corundum powder is 1450°C, and the other methods and parameters are the same as those of material M2;
[0083] Comparative Example DM5: In this comparative example, the sintering temperature of the mixture of mullite particles and corundum powder is 1750°C, and the other methods and parameters are the same as those of material M2;
[0084] Comparative Example DM6: In this comparative example, the sintering time of the mixture of mullite particles and corundum powder is 1.5 h, and the other methods and parameters are the same as those of material M2;
[0085] Comparative Example DM7: In this comparative example, the sintering time of the mixture of mullite particles and corundum powder is 3.5 h, and other methods and parameters are the same as those of material M2.
[0086] Table 3 Corundum mullite ceramic material performance test results
[0087]
[0088]
[0089] It can be seen from Table 3 that when the amount of corundum powder added in the corundum-mullite ceramic material is in the range of 26%-32%, the seismic resistance reaches 82.9%-88.1%; at room temperature, the flexural strength is 538-566MPa, the fracture toughness KIC is 5.2-5.3MPa at room temperature, and the thermal expansion coefficient is 5.9-6.3; at a high temperature of 1000°C, the flexural strength is 599-650.9MPa, the fracture toughness KIC is 6.1-6.4MPa at room temperature, etc. The above-mentioned corundum-mullite ceramic material meets the use requirements of high-temperature insulating materials in thermoelectric conversion devices.
[0090] Under the same other conditions, the thermal shock resistance of the ordinary corundum-mullite ceramic material DM1 prepared from natural corundum and natural kaolin in comparative example D1 is 45%, which is difficult to meet the use requirements of high-temperature insulating materials in nuclear power thermoelectric conversion devices; while the embodiment of the present invention uses high-purity raw materials to meet the use requirements of corundum-mullite ceramics in the field of nuclear power thermoelectric conversion.
[0091] In terms of the mass ratio of corundum micropowder to mullite particles, compared with material M2, the amount of corundum micropowder added in material DM2 is less than 26%, and the amount of corundum micropowder added in material DM3 is higher than 32%. The thermal shock resistance is 74.3% and 76.1% respectively, both of which are difficult to meet the use requirements of corundum mullite ceramics for high-temperature insulating materials when used in the field of thermoelectric conversion for nuclear power. Therefore, the amount of corundum micropowder added in the corundum mullite ceramic material provided by the present invention is preferably 26%-32%.
[0092] In terms of sintering temperature, compared with material M2, the sintering temperature of material DM4 provided by comparative example D4 is less than 1500°C, and the sintering temperature of material DM5 provided by comparative example D5 is greater than 1700°C. The thermal shock resistance of materials DM4 and DM5 are 79.2% and 77.9% respectively, which are difficult to meet the use requirements of high-temperature insulating materials when corundum mullite ceramics are used in the field of thermoelectric conversion for nuclear power. Therefore, the sintering temperature of the corundum mullite ceramic material provided by the present invention is 1500-1700°C.
[0093] In terms of sintering time, compared with material M2, the sintering time of material DM6 provided by comparison example D6 is less than 2.5h, and the sintering time of material DM7 provided by comparison example D7 is greater than 3h. The thermal shock resistance of materials DM6 and DM7 are 76.1% and 74.3% respectively, which are difficult to meet the use requirements of high-temperature insulating materials when corundum mullite ceramics are used in the field of thermoelectric conversion for nuclear power. Therefore, the sintering time of the corundum mullite ceramic material provided by the present invention is 3-3.5h.
[0094] The microstructure of the above-mentioned corundum-mullite ceramic M2 is as follows: Figure 2 As shown, from Figure 2 It can be clearly seen that the corundum-mullite ceramic M2 is composed of corundum phase and mullite phase, and the uniform distribution of elements indicates that the two are evenly distributed.
[0095] Example 2 Heterogeneous component and manufacturing method
[0096] This embodiment provides a corundum mullite ceramic-molybdenum metal heterogeneous component S1-S3 and a brazing manufacturing method thereof. The heterogeneous components S1-S3 are mainly stacked by the corundum mullite ceramic material layer and the molybdenum metal layer, and the interface between the two is connected by brazing to form a brazed joint. The corresponding relationship between the heterogeneous components S1-S3 and the corundum mullite ceramic materials M2, M4-M5 is: S1-M2, S2-M4, S3-M5.
[0097] The corundum mullite ceramic-molybdenum metal heterogeneous components S1-S3 are mainly prepared by the following steps:
[0098] (1) Preparation of brazing materials: Select AgCuTi foil with a thickness of 0.09 mm to 0.1 mm;
[0099] (2) Roughening pretreatment: The surfaces of the corundum-mullite ceramics M1-M5 were polished with 180-mesh sandpaper, and the surfaces of the corundum-mullite ceramics after polishing were rough, thereby obtaining roughened ceramic materials;
[0100] (3) Assembly and fixation: The roughened ceramic material is assembled with molybdenum metal (purity of 99.95% or more) respectively, and the AgCuTi foil brazing material is placed between the corundum mullite ceramic material layer and the molybdenum metal layer, maintaining a spacing of 0.1 mm, and fixed with a clamp to ensure that no movement or deformation occurs during the brazing process, thereby obtaining an assembled component;
[0101] (4) Brazing heating: placing the above-mentioned assembly into a vacuum brazing furnace for heating and brazing to form a brazing joint at the connection interface between the roughened ceramic material and the molybdenum metal. After the heating is completed, a semi-finished heterogeneous welded component is obtained; wherein the heating temperature is 900° C., the holding time is about 25 min, and the heating rate is 10° C. / min;
[0102] (5) Cooling and post-processing: First, maintain the cooling rate at 5°C / min-10°C / min to gradually cool the semi-finished brazed parts of the heterogeneous welding components to room temperature; then perform trimming, polishing and other treatments on the brazed connection parts to ensure that the connection quality meets the requirements, and obtain the heterogeneous components S1-S3.
[0103] This embodiment also provides a thermoelectric conversion device for nuclear power, including the above-mentioned heterogeneous components S1-S3, and the molybdenum metal in the heterogeneous components is an electrode, and the corundum mullite ceramic material is an insulating layer.
[0104] Comparison of heterogeneous components
[0105] The heterogeneous component comparison examples 1-7 each provide a heterogeneous component D1-D8, and the brazing manufacturing method thereof is the same as the manufacturing method provided in Example 2, the main difference being that the comparison examples D1-D7 respectively use corundum mullite ceramic materials DM1-DM7; specifically, the corresponding relationship between the heterogeneous components D1-D7 and the corundum mullite ceramic materials DM1-DM7 is D1-DM1, D2-DM2, D3-DM3, D4-DM4, D5-DM5, D6-DM6, and D6-DM7; the comparison example D8 uses the existing alumina ceramics (Yongzhou Mingrui Ceramic Technology Co., Ltd., 99 alumina ceramics) instead of the corundum mullite ceramic material M2.
[0106] Brazing joint performance test
[0107] The brazed joints of the above-mentioned ceramic-molybdenum metal heterogeneous components S1-S3 and D1-D8 were tested for flexural strength and fracture toughness at room temperature (25°C) under normal conditions, and flexural strength, thermal shock resistance and other performance tests were performed after 100 cycles of rapid cooling from room temperature to 1000°C in air. The results are shown in Table 4.
[0108] Table 4 Performance test results of brazed joints of heterogeneous components
[0109] sample Bending strength / MPa Fracture toughness / MPa Bending strength after 100 times of rapid cooling / MPa Thermal shock resistance / % S1 380 5.2 334 88.12% S2 362 5.4 310 85.7% S3 361 5.3 299 82.9% D1 281 2.2 140 45% D2 346 5.4 257 74.3% D3 349 5.2 265 76.1% D4 309 5.0 244 79.2% D5 325 4.9 253 77.9% D6 315 4.9 239 76.1% D7 340 4.6 104 30.8% D8 360 4.5 38.9 10.8%
[0110] It can be seen from Table 4 that: compared with the comparative example, embodiments S1-S5 use corundum mullite ceramic materials M1-M5 as ceramic insulating materials, so that the brazed joints in the heterogeneous components have excellent mechanical strength. The bending strength of the brazed joints at room temperature is 361-380 MPa, and the fracture toughness KIC is 5.2-5.4 MPa. After 100 times of rapid cooling, the bending strength of the brazed joints is 299-334 MPa, and the thermal shock resistance is 82.9-88.12%, etc., which meet the use requirements of nuclear power thermoelectric conversion devices for high temperature resistant insulating materials, and the ceramic-molybdenum metal heterogeneous component S1 has the best comprehensive performance.
[0111] 2) Structure of brazed joint area of heterogeneous components
[0112] Scanning electron microscopy (SEM) was used to photograph the microstructure of the brazed joint area of ceramic-molybdenum metal heterogeneous components S1 and D8 after 100 cycles of room temperature-1000℃ air quenching treatment. Figure 3 and Figure 4 shown.
[0113] from Figure 3 It can be seen that the brazing joint area between the corundum mullite ceramic and the molybdenum metal heterogeneous component S1 is well brazed without pores and cracks. The structure of the corundum mullite ceramic side is dense, and after 100 air quenching tests, there are no cracks in the brazing joint area and the corundum mullite ceramic side.
[0114] Figure 4 The results show that the alumina ceramic and molybdenum metal brazing joint area are well bonded, without defects such as pores and cracks. However, after 100 air quenching tests, continuous cracks appeared on the alumina ceramic side, proving that during the rapid heating and cooling process of the alumina ceramic-molybdenum metal component, thermal stress was generated inside the material, causing cracks on the alumina ceramic side. Therefore, alumina ceramics cannot meet the thermal shock resistance requirements of thermoelectric conversion devices for insulating materials.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A corundum mullite ceramic material, characterized in that: The main crystal phases are corundum and mullite, and the corundum micropowder and mullite are sintered at high temperature. The flexural strength of the corundum-mullite ceramic is ≥500MPa, and the thermal shock resistance of 100 times of extremely cold air at room temperature-1000℃ is ≥80%.
2. The corundum-mullite ceramic material according to claim 1, characterized in that: The relationship between its thermal shock resistance and its process parameters satisfies the following formula: R=R0+1.34T+3.2ω-4.2×10 -4 T 2 -0.052h 2 ; Among them, R is thermal shock resistance, %; T is sintering temperature, ℃; ω is the mass ratio of corundum micropowder used, %; R0 = -1030.
3. The corundum-mullite ceramic material according to claim 1 or 2, characterized in that: The mass proportion of the corundum micropowder is 26-32%, the particle size of the mullite particles is 180-200 mesh, and the particle size of the corundum micropowder is 200-240 mesh.
4. The corundum-mullite ceramic material according to claim 3, characterized in that: The sintering temperature is 1500℃-1700℃, and the sintering time is 2.5-3.0 h.
5. A method for manufacturing a corundum-mullite ceramic-molybdenum metal heterogeneous component, comprising the steps of: Roughening pretreatment: roughening the surface of the corundum-mullite ceramic material according to any one of claims 1 to 4 to obtain a pretreated corundum-mullite ceramic; Brazing: The pretreated corundum mullite ceramic and molybdenum metal are brazed and connected by a brazing material to obtain the corundum mullite ceramic-molybdenum metal heterogeneous component.
6. The manufacturing method according to claim 5, characterized in that: Calculated by mass percentage, the brazing material includes Zr: 24-28%, Ni: 22-26%, Cu: 24-27%, and the balance is Ti.
7. The manufacturing method according to claim 6, characterized in that: The steps of the brazing process include: Component assembly and fixation: Assemble and fix the pre-treated corundum mullite ceramics and molybdenum metal together to form an assembly component; Brazing heating: using a vacuum brazing furnace to heat and weld the assembly components to form the welding joint, and to obtain a heterogeneous welded component semi-finished product, wherein the heating temperature is 890-910° C. and the holding time is 20-30 min; Cooling and post-processing: Cooling the heterogeneous welded component semi-finished product to room temperature and performing post-processing to obtain the corundum mullite ceramic-molybdenum metal heterogeneous component; wherein the cooling rate during the cooling process is 5°C / min-10°C / min.
8. A corundum-mullite ceramic-molybdenum metal heterogeneous component manufactured by the manufacturing method according to any one of claims 5 to 7, wherein the brazing joint strength at the welding interface of the corundum-mullite ceramic material and the molybdenum metal is ≥350 MPa.
9. Use of the corundum-mullite ceramic-molybdenum metal heterogeneous component according to claim 8 in a thermoelectric conversion device.
10. A thermoelectric conversion device for nuclear power, characterized in that: The invention comprises the corundum-mullite ceramic-molybdenum metal heterogeneous component as claimed in claim 8.